Studi Literatur: Implementasi Model Based Learning (PBL) Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa SD - Denisa Azura; Sahrun Nisa; Ari Suriani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This research aims to find out how the implementation of problem-based learning model to improve elementary school students' math problem solving skills. PBL, as a learning model, challenges students to develop critical and analytical thinking skills when facing problems related to the subject matter being taught. The method used in this research is the literature study method (library research). This research applies qualitative methods in its approach” Data collection was conducted through a literature review, with a focus on tracing scientific articles relevant to the research context. After analyzing ten journal articles, it was found that the application of the Problem-Based Learning (PBL) model has a positive impact on improving mathematical problem-solving skills at various levels of primary school, both in the early grades and at higher levels. In its application, the Problem-Based Learning (PBL) model positively influences students' ability to solve mathematical problems. PBL facilitates students' critical and analytical thinking, improves analytical skills and problem-solving abilities, and also strengthens teamwork and communication. The results of this study confirm that the use of PBL can improve elementary school students' ability to solve mathematical problems and potentially improve their academic achievement.